Three-dimensional structure of herpes simplex virus from cryo-electron tomography. - Grünewald, K; Desai, P; Winkler, D; Heymann, J; Belnap, D; Baumeister, W; Steven, A (2003)
Herpes simplex virus, a DNA virus of high complexity, consists of a nucleocapsid surrounded by the tegument-a protein compartment-and the envelope. The latter components, essential for infectivity, are pleiomorphic. Visualized in cryo-electron tomograms of isolated virions, the tegument was seen to form an asymmetric cap: On one side, the capsid closely approached the envelope; on the other side, they were separated by approximately 35 nanometers of tegument. The tegument substructure was particulate, with some short actin-like filaments. The envelope contained 600 to 750 glycoprotein spikes that varied in length, spacing, and in the angles at which they emerge from the membrane. Their distribution was nonrandom, suggesting functional clustering.